2005
DOI: 10.1536/ihj.46.619
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Cholesterol and Mortality in Heart Failure Comparison Between Patients With and Without Coronary Artery Disease

Abstract: SUMMARYHypercholesterolemia is a risk factor for development of coronary artery disease (CAD), however, several reports have suggested that low serum cholesterol is associated with a worse prognosis in patients with congestive heart failure (CHF). The objective of this study was to determine the prognostic value of cholesterol for CHF. The study subjects consisted of 133 consecutive patients hospitalized in our institution for progressive heart failure from April 2000 to March 2003. Thirty-two percent of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 23 publications
0
14
2
Order By: Relevance
“…The relationship between LDL levels and HF outcomes among the elderly, which we document here, seems to be contradictory to the findings in patients with coronary artery disease [5,6,7,8,9] and in patients enrolled in other HF studies [8,9,11,18,19]. Several studies reported that patients with ischemic and nonischemic HF appear to have an opposite pattern (‘reverse epidemiology'), with low levels being associated with a worse prognosis independent of other prognostic factors [13,20].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The relationship between LDL levels and HF outcomes among the elderly, which we document here, seems to be contradictory to the findings in patients with coronary artery disease [5,6,7,8,9] and in patients enrolled in other HF studies [8,9,11,18,19]. Several studies reported that patients with ischemic and nonischemic HF appear to have an opposite pattern (‘reverse epidemiology'), with low levels being associated with a worse prognosis independent of other prognostic factors [13,20].…”
Section: Discussioncontrasting
confidence: 99%
“…Weight loss (not edematous) and cardiac cachexia are well-known independent risk factors for HF mortality. Unlike the results of other studies [9,14,19,21], our elderly patients with a range of LDL levels had the same normal albumin, creatinine, hemoglobin and body mass index values which are established markers of the nutritional state. They also had normal levels of the inflammatory marker, C-reactive protein.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Under the last condition, the biosurfactant can block the active form of the protein, thus making the catalytic site accessible to the inhibitor . The elevation of serum lipids is usually associated with diabetes mellitus, which is the major risk factor of coronary heart diseases . The risk of the development of atherosclerosis in diabetes mellitus can be reduced by elevating HDL‐cholesterol level .…”
Section: Discussionmentioning
confidence: 99%
“…[3,4] Theoretically, reducing TC and LDL-C levels would not only decrease the incidence of CHD as evidenced by previous clinical trials but may also improve HF patients’ outcomes. Nevertheless, 2 randomized controlled trials showed no mortality benefit of rosuvastatin therapy in HF patients, [5,6] despite substantial reduction of TC and LDL-C was achieved.…”
Section: Introductionmentioning
confidence: 99%